2002
DOI: 10.1073/pnas.162356099
|View full text |Cite
|
Sign up to set email alerts
|

Identification of oncogenes collaborating with p27 Kip1 loss by insertional mutagenesis and high-throughput insertion site analysis

Abstract: The p27 Kip1 protein is a cyclin-dependent kinase inhibitor that blocks cell division in response to antimitogenic cues. p27 expression is reduced in many human cancers, and p27 functions as a tumor suppressor that exhibits haploinsufficiency in mice. Despite the well characterized role of p27 as a cyclin-dependent kinase inhibitor, its mechanism of tumor suppression is unknown. We used Moloney murine leukemia virus to induce lymphomas in p27؉͞؉ and p27؊͞؊ mice and observed that lymphomagenesis was accelerated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 30 publications
(34 reference statements)
2
109
2
Order By: Relevance
“…We and others reported that JDP2 is an AP-1 transcriptional repressor 15,[17][18][19][20] with histone-chaperone activity that inhibits histone acetylation by recruiting HDAC3. 24 JDP2 also inhibited the RA-dependent differentiation of embryonic carcinoma F9 cells.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We and others reported that JDP2 is an AP-1 transcriptional repressor 15,[17][18][19][20] with histone-chaperone activity that inhibits histone acetylation by recruiting HDAC3. 24 JDP2 also inhibited the RA-dependent differentiation of embryonic carcinoma F9 cells.…”
Section: Discussionmentioning
confidence: 91%
“…12,13 Jun dimerization protein 2 (JDP2) is a DNA-binding protein that forms homodimers or heterodimers with c-Jun, ATF2 and C/EBPg. [14][15][16] JDP2 can function not only as a transcriptional repressor but also as a coactivator in various types of cell, 15,[17][18][19][20] and it is involved in a variety of biological phenomena such as proliferation and differentiation of cells and apoptosis. 14,15,17,18,[20][21][22] For example, forced expression of JDP2 represses the retinoic acid-mediated (RA-mediated) transcription of the c-jun gene and the differentiation of F9 cells in response to RA.…”
mentioning
confidence: 99%
“…In contrast to other studies using the MMLV or in the AKXD or BXH2 inbred mouse lines to accelerate pre-T and pre-B lymphomas or myeloid leukemias (Li et al, 1999;Hwang et al, 2002;Kim et al, 2003;Erkeland et al, 2004;Iwasaki et al, 2004;Shin et al, 2004), this approach exploited the preferential tropism of the mAIDS virus for mature B lymphocytes and successfully accelerated cancer progression in IgHm-HOX11 Tg mice. The relatively low number of integrations observed (B1.9 per tumor) is consistent with reports that the Du5H mAIDS virus yields fewer (between 2 and 4) integration events when compared to MMLV (between 6 and 10) or with other models of recombinant inbred mouse strains characterized by laterally transmitted retroviruses (Huang et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Retroviral-derived DNA sequences that integrate adjacent to cellular oncogenes or within coding regions of tumor suppressors, can result in altered host gene expression contributing, ultimately, to clonal expansion of the infected cell. While the proviral tagging approach has resulted in the discovery of many genes involved in lymphoid and myeloid leukemias (Li et al, 1999;Hwang et al, 2002;Kim et al, 2003;Erkeland et al, 2004;Iwasaki et al, 2004;Shin et al, 2004), less work has been conducted on mature B-cell lymphomas.…”
Section: Introductionmentioning
confidence: 99%
“…11 reside the genes Dph1, Cis8 and Pps. Integration into a region spanning 4 kb to 23 kb 5′ of Dph1, which would be predicted to interrupt mmu-miR-132 results in T cell lymphomas [77,78]. Located a little further distal on chr.…”
Section: Mouse Mirnas and Genomic Locationmentioning
confidence: 99%